Pseudoterranova decipiens species A and B (Nematoda, Ascaridoidea): nomenclatural designation, morphological diagnostic characters and genetic markers - PAGGI, Lia; MATTIUCCI, Simonetta; CIANCHI, Maria Rossella; BULLINI, Luciano; David I. Gibson; Bjorn Berland; Giuseppe Nascetti (KLUWER ACADEMIC PUBL, 2000)
Five genetically distinct and reproductively isolated species have been detected previously within the morphospecies Pseudoterranova decipiens from the Arctic-Boreal, Boreal and Antarctic. Morphological analysis was carried out on male specimens identified by genetic (allozyme) markers, allowing the detection of significant differences at a number of characters between two members of the P. decipiens complex, namely P. decipiens A and B. On the basis of such differences, the nomenclatural designation for the two species is discussed. The names Pseudoterranova krabbei n. sp. and P. decipiens (sensu stricto) are proposed for species A and B, respectively. Morphological and genetic differentiation between the two species is shown using multivariate analysis. Allozyme diagnostic keys for routine identification of the four members of the P. decipiens complex, namely P. decipiens (s.s.), P. krabbei, P. bulbosa and P. azarasi, irrespective of sex and life-history stage, are provided.